ESTRATÉGIAS DE IRRIGAÇÃO COM DÉFICIT HÍDRICO NOS ESTÁDIOS FENOLÓGICOS DO FEIJÃO-CAUPI SOB ADUBAÇÃO POTÁSSICA - Soares, Lauriane Almeida dos Anjos; Layse Freitas Medeiros, Thamara; Cristina Gomes Colman, Victoria; Victor de Sousa Palmeira, Irlan; José da Silva, Idelvan; Carantino Lucena Moreira, Romulo (IRRIGA, 2021)
ESTRATÉGIAS DE IRRIGAÇÃO COM DÉFICIT HÍDRICO NOS ESTÁDIOS FENOLÓGICOS DO FEIJÃO-CAUPI SOB ADUBAÇÃO POTÁSSICA LAURIANE ALMEIDA DOS ANJOS SOARES1; THAMARA LAYSE FREITAS MEDEIROS2; VICTORIA CRISTINA GOMES COLMAN3; IRLAN VICTOR DE SOUSA PALMEIRA4; IDELVAN JOSÉ DA SILVA5 E ROMULO CARANTINO LUCENA MOREIRA6 1 Unidade Acadêmica de Ciências Agrárias, Universidade Federal de Campina Grande, UFCG, Rua Jario Vieira Feitosa, 1770, Bairro dos Pereiros, Pombal, PB, Brasil. E-mail: laurispo.agronomia@gmail.com 2 Unidade Acadêmica de Ciências Agrárias, Universidade Federal de Campina Grande, UFCG, Rua Jario Vieira Feitosa, 1770, Bairro dos Pereiros, Pombal, PB, Brasil. E-mail: thamaraamedeiross@gmail.com 3 Unidade Acadêmica de Ciências Agrárias, Universidade Federal de Campina Grande, UFCG, Rua Jario Vieira Feitosa, 1770, Bairro dos Pereiros, Pombal, PB, Brasil. E-mail: vikcolman@gmail.com 4 Unidade Acadêmica de Ciências Agrárias, Universidade Federal de Campina Grande, UFCG, Rua Jario Vieira Feitosa, 1770, Bairro dos Pereiros, Pombal, PB, Brasil. E-mail: irlan7764@gmail.com 5 Unidade Acadêmica de Engenharia Agrícola, Universidade Federal de Campina Grande, UFCG, Rua Aprígio Veloso, 882 -Universitário, Campina Grande, PB, Brasil. E-mail: idelvan3@hotmail.com 6 Unidade Acadêmica de Engenharia Agrícola, Universidade Federal de Campina Grande, UFCG, Rua Aprígio Veloso, 882 -Universitário, Campina Grande, PB, Brasil. E-mail: romulocarantino@gmail.com 1 RESUMO Palavras-chave: Vigna unguiculata L., tolerância à seca, nutrição mineral SOARES, L. A. dos A.; MEDEIROS, T. L. F.; COLMAN, V. C. G.; PALMEIRA, I. V. de S.; SILVA, I. J. da; MOREIRA, R. C. L. IRRIGATION STRATEGIES WITH WATER DEFICIT IN THE PHENOLOGICAL STAGES OF THE COWPEA UNDER POTASSIC FERTILIZATION 2 ABSTRACT In semi-arid regions, water deficiency is the main environmental factor that influences the yield of plants, in these regions the proper management of resources is essential in order to guarantee the sustainability of the production system. Thus, this study aimed to evaluate the morphology and phytomass partition of cowpea (Vigna unguiculata L.), to cultivate BRS Marataoã, when submitted to water deficit management strategies in different phenological stages of the crop and fertilization doses potassium. A randomized block design was used, in a 5 x 5 factorial scheme, with three replications, with the treatments being defined according to the five potassium fertilization doses (50, 75, 100, 125, and 150% of K2O) associated with five water deficit management strategies at the different phenological stages of the crop. The application of water deficit associated with potassium doses favored the growth and accumulation of phytomass in the flowering phase. Increasing doses of potassium when associated with water deficit in the flowering and fruiting stages compromise the number of pods and pod length. In the early stages of the development of cowpea, irrigation with water deficit can be applied without significant losses in the production components. Keywords: Vigna unguiculata L., drought tolerance, mineral nutrition